Iron Deficiency Prevention and Dietary Habits Among Elite Female University Athletes in Japan - Hiromi Inaba; Haruo Hanawa; Fumi Hoshino; Mutsuaki Edama; Go Omori (Sports, 2025)
This study investigated the percentage of iron deficiency anemia (IDA) and iron deficiency (ID) among 71 elite female athletes at a Japanese university and assessed their dietary habits. IDA was identified in 9.9% (n = 7) of participants, and only 22.5% (n = 16) self-reported dietary practices aimed at preventing or managing ID/IDA. Notably, 52.1% (n = 37) of the athletes exhibited IDA or ID but lacked an appropriate dietary approach. Moreover, even among those who reported an intentional dietary approach to the prevention or management of ID/IDA, the intake of iron- and vitamin C-rich foods was insufficient, limiting the effectiveness of their efforts. These findings highlight a gap between awareness and effective practice, indicating that many female athletes in Japan, despite being at elevated risk, do not follow evidence-based dietary strategies for preventing or treating ID/IDA. Targeted nutritional education and routine screening of iron status are strongly recommended for this population.